BIOSTRATIGRAFI DAN PALEOEKOLOGI WILAYAH LEPAS PANTAI BARAT DAYA SUMBA SEJAK PLEISTOSEN AKHIR BERDASARKAN KUMPULAN FORAMINIFERA PLANKTONIK - Ardi, Ryan Dwi Wahyu; Maryunani, Khoiril Anwar; Yulianto, Eko; Putra, Purna Sulastya; Nugroho, Septriono Hari (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
Foraminifera are microfaunas/microfossils that frequently applied in geology especially for biostratigraphy and paleoecological analysis. This research aim to create biozonation and paleoecological analysis in the region off the southwest coast of Sumba based on planktonic foraminiferal assemblages. This region heavily affected by northwest monsoon – southeast monsoon shift and located next to one of the ITF’s outflow paths (Ombai Strait – Savu Sea) which eventually form its ecological condition. A 235 cm long deep sea sediment core coded ST08 will be used as research material. Foraminifera specimens were determined quantitatively by observing approximately 300 specimens for each split. Each taxon determined from that part then calculated for each individu that was found while different taxa determined from other splits are considered to be one. Biozonation was determined based on either Blow biozonation or Bolli and Saunders biozonation. One zone was obtained based on Blow biozonation which is N23 zone, equal to Pleistocene – Holocene. Two zones were determined based on Bolli and Saunders biozonation which are Globigerinella calida – Clavarotella bermudezi zone (below 147 cm depth), equal to Late Pleistocene and Globorotalia fimbriata zone (0 – 147 cm depth), equal to Holocene. Paleocological analysis focused on the thermocline depth parameter inferred from the relative abundance of thermocline dweller taxa that consist of Neogloboquadrina dutertrei, Puleniatina obliqueloculata, and Globorotalia menardii. Themocline dweller abundance were relatively higher during Pleistocene (49,76 – 75,66%, average 60,01%), indicating shallower thermocline (eutropic condition) while during Holocene its abundance relatively lower (33,90 – 57, 17%, average 45,77%), which indicated thermocline deepening (more oligotropic condition). Those conditions were related to the southeast monsoon domination during Pleistocene (stronger ITF) before its weakening on Holocene which induced northwest monsoon strengthening (weaker ITF).